The Influence of Interactive Learning Media Based on Ispring Suite 11 on Physics Learning Outcomes on Gas Kinetic Theory Material at SMA Negeri 25 Garut - Solihati, Essy; Darmawan, Deni; Fauzi Nursiami, Eva; Misbahudin, Misbahudin; Nuryadi, Adi (Green Publisher Indonesia, 2024)
This research is motivated by the importance of learning media that is tailored to the needs of students, one of which is in the process of improving learning outcomes. This research was conducted because of the low learning outcomes of students in physics subjects, one of which is due to the use of learning media in the classroom, which still tends to use conventional learning media. Therefore, efforts are needed so that student learning outcomes can be improved. Interactive learning media based on ispring suite 11 is an interesting learning medium and allows students to actively participate in learning activities and improve student learning outcomes. The purpose of this study is to determine the influence of interactive learning media based on ispring suite 11 on physics learning outcomes on gas kinetic theory material. The type of research used is Quasy Experimental with the design of ''Nonequivalent Pretest and Posttest Control Group'', samples are selected by purposive sampling technique. Class XI Science 3 is used as an experimental class and Class XI Science 1 is used as a control class. The instruments used were tests with multiple choice of 20 questions and questionnaires. Based on the calculation using the effect size, a value of 1.36 was obtained which was categorized as very strong, so it was proven that ispring suite 11-based interactive learning media had a significant influence on student learning outcomes. And the results of the study show that interactive learning media based on ispring suite 11 is proven to be effective in improving student learning outcomes compared to conventional media, this is seen from the results of the N-gain test in the experimental class of 71.05% and in the control class of 54.24%.